Notalgia paresthetica: the unreachable itch - Carolyn Ellis (Mattioli1885, 2013)
Background: Notalgia paresthetica (NP) is a very common, under-recognized condition characterized by pruritus in a unilateral, dermatomal distribution in the mid-back. Chronic pruritus is sometimes accompanied by pain, paresthesias, or altered sensation to touch. Objectives: To review the current literature with regards to the cause of NP and its most appropriate treatment. Methods: Comprehensive literature review using PubMed to inspect the available data on NP. Results: The most likely cause of NP is cutaneous nerve damage. Many therapies have been tried in the treatment of NP, mostly in small case studies. Conclusions: The published cases and studies suggest symptoms of NP are due to a cutaneous sensory neuropathy. Treatments addressing the condition as such are more successful than traditional itch therapies. In many cases, a simple explanation for the persistent pruritus is satisfactory for patients. For very distressing cases, therapy should address the condition as a benign sensory neuropathy. Further studies are needed to evaluate which treatments have the greatest potential for providing symptom relief.